Education, Ranking, and Competition for Jobs - Moen, Espen R. (Journal of Labor Economics, 1999)
I study workers' incentives to invest in general human capital (education) in the presence of search‐induced unemployment. Workers queue for jobs, and firms prefer to hire the most productive applicants because of rent sharing. As a result, an unemployed worker's ranking relative to other job seekers will influence his job‐finding rate. This creates a “rat race,” where workers invest in education partly in order to achieve a better ranking. In equilibrium, identical workers may have incentives to diversify in terms of education, and the investments in education may exceed the socially optimal level.